2009
DOI: 10.1371/journal.pone.0005683
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Deep Sequencing Reveals Dynamic HIV-1 Escape and Large Population Shifts during CCR5 Antagonist Therapy In Vivo

Abstract: High-throughput sequencing platforms provide an approach for detecting rare HIV-1 variants and documenting more fully quasispecies diversity. We applied this technology to the V3 loop-coding region of env in samples collected from 4 chronically HIV-infected subjects in whom CCR5 antagonist (vicriviroc [VVC]) therapy failed. Between 25,000–140,000 amplified sequences were obtained per sample. Profound baseline V3 loop sequence heterogeneity existed; predicted CXCR4-using populations were identified in a largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
218
4
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(238 citation statements)
references
References 32 publications
9
218
4
3
Order By: Relevance
“…Recent studies have demonstrated that ultradeep sequencing is a more sensitive and effective tool for detecting variants in viral quasispecies than conventional direct PCR sequencing, because ultradeep sequencing can identify low-abundance variants (1,17,18,40). Moreover, ultradeep sequencing is not only useful for the detection but also the quantification of variants in the viral quasispecies pool (41,42). Therefore, the true prevalence of variants in viral quasispecies that may be clinically relevant can be determined with ultradeep sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that ultradeep sequencing is a more sensitive and effective tool for detecting variants in viral quasispecies than conventional direct PCR sequencing, because ultradeep sequencing can identify low-abundance variants (1,17,18,40). Moreover, ultradeep sequencing is not only useful for the detection but also the quantification of variants in the viral quasispecies pool (41,42). Therefore, the true prevalence of variants in viral quasispecies that may be clinically relevant can be determined with ultradeep sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are concerns that the incidence of CXCR4-tropic HIV has increased in several countries (34,35). The introduction and distribution of CCR5 antagonists for HIV treatment may help the emergence of CXCR4-tropic HIV (36)(37)(38). These findings support the idea that blocking both CCR5 and CXCR4 is needed to prevent HIV transmission.…”
mentioning
confidence: 70%
“…Standard genotyping methods detect mutants of dominant species or give a composite of HIV sequences present but are generally unable to detect low frequency mutants that comprise less than 20% of the total HIV population [92,93]. Ultra-deep sequencing (UDS) technologies, such as pyrosequencing, polymerase-based sequencing-by-synthesis and ligase-based sequencing, have the ability to generate data on hundreds of millions of base pairs within a few days [94,95], characterize genotypic diversity, analyze tropisms, and accurately discern rare and drugresistant strains circulating in the population that could potentially cause treatment failure after ART is initiated [96,97]. In studies aimed at detecting and characterizing HIV variants, UDS methods were able to detect a greater proportion of low frequency sequence variants when compared with conventional PCR sequencing methods [97,98], and there is evidence that UDS may be able to detect mutations present in only 1-2% of the population [93,94].…”
Section: Hiv Monitoring and Managementmentioning
confidence: 99%